Investigation of CRISPR/Cas9-induced SD1 rice mutants highlights the importance of molecular characterization in plant molecular breeding. (20th May 2020) - Biswas, Sukumar; Tian, Jiaqi; Li, Rong; Chen, Xiaofei; Luo, Zhijing; Chen, Mingjiao; Zhao, Xiangxiang; Zhang, Dabing; Persson, Staffan; Yuan, Zheng; Shi, Jianxin
Abstract: Although Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated 9 (Cas9) system has been widely used for basic research in model plants, its application for applied breeding in crops has faced strong regulatory obstacles, due mainly to a poor understanding of the authentic output of this system, particularly in higher generations. In this study, different from any previous studies, we investigated in detail the molecular characteristics and production performance of CRISPR/Cas9-generated SD1 ( semi-dwarf 1 ) mutants from T2 to T4 generations, of which the selection of T1 and T2 was done only by visual phenotyping for semidwarf plants. Our data revealed not only on- and off-target mutations with small or lager indels but also exogenous elements in T2 plants. All indel mutants passed stably to T3 or T4 without additional modifications independent on the presence of Cas9, while some lines displayed unexpected hereditary patterns of Cas9 or some exogenous elements. In addition, effects of various SD1 alleles on rice height and yield differed depending on genetic backgrounds. Taken together, our data showed that the CRISPR/Cas9 system is effective in producing homozygous mutants for functional analysis, but it may be not as precise as expected in rice, and that early and accurate molecular characterization and screening must be carried out for generations before transitioning of the CRISPR/Cas9 system from laboratory to field.